Seasonal fears - McGuire, Seanan (Alchemical journeys, 2022)
"From New York Times bestselling author Seanan McGuire, Seasonal Fears is the extraordinary companion novel to Middlegame. The king of winter and the queen of summer are dead. The fight for their crowns begins! Melanie has a destiny, though it isn't the one everyone assumes it to be. She's delicate; she's fragile; she's dying. Now, truly, is the winter of her soul. Harry doesn't want to believe in destiny, because that means accepting the loss of the one person who gives his life meaning, who brings summer to his world. So, when a new road is laid out in front of them-a road that will lead through untold dangers toward a possible lifetime together-walking down it seems to be the only option. But others are following behind, with violence in their hearts. It looks like Destiny has a plan for them, after all.... "One must maintain a little bit of summer even in the middle of winter." -Thoreau"--